2002
DOI: 10.1074/jbc.m110377200
|View full text |Cite
|
Sign up to set email alerts
|

Heat Induction of the Unphosphorylated Form of Hypoxia-inducible Factor-1α Is Dependent on Heat Shock Protein-90 Activity

Abstract: Hypoxia-inducible factor (HIF)-1␣ is the oxygen-sensitive subunit of HIF-1, a transcriptional master regulator of oxygen homeostasis. Oxygen-dependent prolyl hydroxylation targets HIF-1␣ for ubiquitinylation and proteasomal degradation. Unexpectedly, we found that exposing mice to elevated temperatures resulted in a strong HIF-1␣ induction in kidney, liver, and spleen. To elucidate the molecular mechanisms responsible for this effect, HepG2 hepatoma cells were exposed to different temperatures (34 -42°C) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
136
1
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 45 publications
2
136
1
3
Order By: Relevance
“…Binding of HIF-1a with Hsp90 prevents HIF-1a from degradation (33,34). We found that chrysin inhibited binding of HIF-1a to Hsp90 (Fig.…”
Section: Chrysin Inhibits Hif-1a Expression Via Reducing Its Stabilitymentioning
confidence: 67%
See 1 more Smart Citation
“…Binding of HIF-1a with Hsp90 prevents HIF-1a from degradation (33,34). We found that chrysin inhibited binding of HIF-1a to Hsp90 (Fig.…”
Section: Chrysin Inhibits Hif-1a Expression Via Reducing Its Stabilitymentioning
confidence: 67%
“…2C. Hsp90, a chaperone protein, has been shown to stabilize HIF-1a (34,44). Chrysin was found to inhibit the binding of HIF-1a to Hsp90, suggesting that chrysin inhibits HIF-1a expression via interfering with the interaction between HIF-1a and Hsp90 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the PHDs ideally suited to regulate HIFα protein levels over a wide range of physiologically relevant oxygen concentrations. Indeed, when we designed immunoblotting experiments for maximal sensitivity, it was possible to detect HIF-1α already under normoxic conditions, in line with a limited PHD activity [18]. Consistent with this observation, HIF-1α-deficient cells display reduced gene expression of HIF-1 target genes even when cultured under normoxic conditions, when HIF-1α protein levels normally are not detectable by immunoblotting [19][20][21].…”
mentioning
confidence: 58%
“…Geldanamycin, a benzoquinone ansamycin antibiotic and natural product of Streptomyces geldanus, possesses antitumor activity and specifically binds with high affinity to ATP-binding sites of Hsp90 (Lewis et al 2000;Katschinski et al 2002;Nomura et al 2004). Previous studies have established that Hsp90 inhibitors are particularly toxic to tumor cells because of a presumed increased binding affinity for these drugs and an enhanced Hsp90 reliance of genetically unstable tumor cells.…”
Section: Discussionmentioning
confidence: 99%